Pattern of the news media consumption and news discussion among youth : a test of agenda setting theory - Wok, Saodah; Tamam, Ezhar; Bolong, Jusang (2011)
There have been many studies in the media consumption habits among youth. Previous studies reported that youth preferred news on online media compared to other news media. This study tries to explore the pattern of news media consumption and interpersonal news discussions. The specific objectives of the study are (1) to determine the level of perceived news media credibility, (2) to find out the level of news media consumption, (3) to find out the extent of interpersonal news discussions, (4) to analyze the relationship between perceived media credibility and news media consumption with interpersonal news discussions, and (5) to differentiate between selected demographic characteristic with news media consumption and interpersonal news discussions. The study made use of survey research design method. The data were collected using a set ofself-administered questionnaire. A sample of 1363 was randomly selected usingstratified random sample. Malaysian youth aged 15-25 years old were gathered for the study. The data were analyzed using SPSS WIN 16.0. Descriptive and Inferential statistics were used for the study.